‘Femina lectissima’: Giulia, mother of Marco Antonio, between description and representation - Rohr Vio, Francesca (Romanitas - Revista de Estudos Grecolatinos, 2018)
The paper reconstructs the biography of Iulia, Mark Antony’s mother, and analyzes the representation of the matron in the literary tradition. Firstly, it investigates how the particular conditions of the late Republic influenced Iulia’s realisation of innovative initiatives with respect to the feminine model and then studies how violations of the mos maiorum were evaluated in the representation of Mark Antony’s mother by of the coeval and later sources. In this perspective the paper analyzes the reasons for the legitimacy of the matron even among authors who are hostile to her son and the issues and the methods of its valorization.